Stress and sleep quality in medical students: a cross-sectional study from Vietnam - Tran, Duc-Si; Nguyen, Duy-Thai; Nguyen, Thai-Hang; Tran, Cao-Thinh-Phuoc; Duong-Quy, Sy; Nguyen, Thanh-Hiep (Frontiers in Psychiatry, 2023)
Background: The COVID-19 pandemic has resulted in significant global social and economic disruptions, as well as changes in personal attitude and behavior. The purpose of this research is to assess the sleep quality and stress levels of medical students. Method: Data was collected from medical students over the course of a month in 2021. A total of 4,677 students at the University of Medicine Pham Ngoc Thach were invited to complete an anonymous web-based survey, which included the Pittsburgh Sleep Quality Questionnaire Index (PSQI) for measuring sleep quality and the COVID-19 Student Stress Questionnaire (CSSQ) for evaluating stress. Results: A total of 1,502 students participated in our survey. More than half of the participants exhibited poor quality of sleep as indicated by their PSQI score. Many students reported going to bed after midnight and spending time on their smartphones. Among the students surveyed, 21.84% experienced low levels of stress (CSSQ ≤6), 63.38% had mild stress (7≤ CSSQ score ≤14), 14.78% reported high levels of stress (CSSQ >14). Conclusion: This study showed a high prevalence of poor sleep quality in the surveyed students, which could be attributed to changes in their behavior following the COVID-19 outbreak. Mild stress was also frequently observed, and it may be related to sleep disorders in this population. These important findings provide valuable insights for making recommendations, including lifestyle modifications to improve sleep quality.